Sustainable Development of Jardhar Village, Uttarakhand, India Through Participatory Learning and Action - Kamble, R. K. (International Journal of Social Sciences and Management, 2014)
Jardhar village is located in the Himalayan range of Chamba block of Tehri Garhwal district of Uttrakhand state of India. The village is divided into 9 wards and 17 hamlets at a stretch of 9 km. The village comprises of about 285 families from general and scheduled caste (2001 census). The participatory learning action (PLA) methodology was adopted for the sustainable development of Jardhar village. A field study was carried out in summer 2013. During filed visit problem matrix analysis was carried out, which revealed 17 problems from the study area. In addition to this, reasons for causes of poverty were also assessed. The problems were ranked according to the priority of villagers from diverse socio-economic background through PLA and suitable S&T interventions were arrived through brainstorming activities. An integrated action plan was prepared which emphasize upon short term and long term measures to be adopted to overcome these problems and to move toward sustainable development of the Jardhar village. The interaction of all these measures for effective implementation has also been suggested. DOI: http://dx.doi.org/10.3126/ijssm.v1i1.8961 Int. J. Soc. Sci. Manage. Vol.1(1) 2014 29-34